Attitude of Learners towards English and Kiswahili in Tanzania - Ideh, Amaka Edith; Tibategeza, Eustard Rutalemwa (NIU Journal of Humanities; Vol 7 No 1 (2022): NIU Journal of Humanities, Vol. 7 No. 1, March 2022DO - 10.58709/niujhu.v7i1.1386, 2022)
Tanzania is a multilingual country like most other African countries with over 120 languages. It is one of the few African countries where indigenous language (Kiswahili) is sole medium of instruction (MoI) throughout primary schools, while English takes over secondary and tertiary education. The importance of these two languages can never be over-emphasised and attitude of learners towards the languages are ambivalent. The study assesses the use of English and Kiswahili in all imaginable communication contexts in the school environment, and extends the assessment to the frequency with which the respondents use English and Kiswahili. This work is part of larger study conducted in Mwanza region, Tanzania. The data for the study were collected from both primary and secondary sources. The primary data for the study were collected by means of questionnaire, interviews, focus group discussions, and observation. The secondary source includes previously published materials related to English and Kiswahili usage in Tanzania schools. The result of this study reveals that more than 85% of the respondents use English either always or often in the classrooms. However, the figure changes when it comes to the language use outside the classroom; Kiswahili dominates virtually in all contexts because it is the only dominant language in and outside the school environments. The study also reveals that the socio-linguistic factor of Tanzania justifies the fact that Kiswahili is the preferred language for majority in different contexts and the only language by which many people interact with a wide range of people from different ethnic groups. The study proposes the use of the two languages in education on the ground that the two languages are important to Tanzanian and the use should be simultaneously. Keywords: Medium of instruction, attitude, Kiswahili, language preference, Tanzania, education.